2015
DOI: 10.1002/pro.2827
|View full text |Cite
|
Sign up to set email alerts
|

From invagination to navigation: The story of magnetosome-associated proteins in magnetotactic bacteria

Abstract: Magnetotactic bacteria (MTB) are a group of Gram-negative microorganisms that are able to sense and change their orientation in accordance with the geomagnetic field. This unique capability is due to the presence of a special suborganelle called the magnetosome, composed of either a magnetite or gregite crystal surrounded by a lipid membrane. MTB were first detected in 1975 and since then numerous efforts have been made to clarify the special mechanism of magnetosome formation at the molecular level. Magnetoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 138 publications
(679 reference statements)
0
30
0
1
Order By: Relevance
“…Magnetotactic bacteria (MTB) are a group of Gram-negative bacteria that align with and move along magnetic fields. The bacterium contains subcellular organelles named magnetosomes, each of which is composed of ~30-120 nm iron-based magnetic particle (magnetite or gregite) enclosed in a protein-rich lipid membrane (Barber-Zucker et al, 2016a;Komeili, 2012;Uebe and Schüler, 2016). The magnetosomes are arranged on an actin-like polymer in a chain arrangement, creating a magnetic dipole moment which allows these bacteria to use external magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetotactic bacteria (MTB) are a group of Gram-negative bacteria that align with and move along magnetic fields. The bacterium contains subcellular organelles named magnetosomes, each of which is composed of ~30-120 nm iron-based magnetic particle (magnetite or gregite) enclosed in a protein-rich lipid membrane (Barber-Zucker et al, 2016a;Komeili, 2012;Uebe and Schüler, 2016). The magnetosomes are arranged on an actin-like polymer in a chain arrangement, creating a magnetic dipole moment which allows these bacteria to use external magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetotactic bacteria such as Magnetospirillum magneticum AMB‐1 are capable of aligning in the earth's magnetic field, which allows them to swim towards sources of oxygen . This is achieved through the formation of magnetosomes, ∼50 nm membrane‐bound cellular compartments in which single magnetite or greigite crystals are biomineralized . Efficient orientation in magnetic fields arises from alignment of multiple magnetosomes, which are positioned in a linear array that acts much like a compass needle.…”
Section: Introductionmentioning
confidence: 99%
“…11 This is achieved through the formation of magnetosomes, 50 nm membrane-bound cellular compartments in which single magnetite or greigite crystals are biomineralized. 12,13 Efficient orientation in magnetic fields arises from alignment of multiple magnetosomes, which are positioned in a linear array that acts much like a compass needle. Alignment of magnetosomes is achieved by apparent binding to a cytoplasmic filament consisting of the magnetosome-specific actin homolog MamK.…”
Section: Introductionmentioning
confidence: 99%
“…The main steps in the process of MS formation are membrane invagination, protein sorting, MS alignment into chains, iron transport, redox control, nucleation, magnetic crystal size, and shape control and chain formation as shown in Fig. . Invagination of the CM is the first step during MS formation.…”
Section: Cell Biologymentioning
confidence: 99%
“…Faivre et al [75] reported that iron, temperature, and pH have significant impact on physiology of bacterial cell, also on microstructural and physical characteristics of magnetite crystals formed by FIGURE 2 Different steps during magnetosomes (MS) chain formation; reproduced with permission from Ref. [66] MTB. However, studies on environmental conditions of MS synthesis by MTB are limited [75].…”
Section: Factors Effecting Crystal Maturation During Ms Formationmentioning
confidence: 99%